Effect of Carbon and Manganese Content on the Microstructure and Mechanical Properties of High Manganese Austenitic Steel - Uğur Gürol; Süleyman Can Kurnaz (Journal of Mining and Metallurgy, Section B: Metallurgy, 2020)
In the present work the influence of Carbon and Manganese on the microstructure and the mechanical properties of high manganese austenitic steel was investigated. Microstructural results showed that increment of carbon and manganese content increased the grain size and amount of carbides in as-cast condition. The solution annealing fully dissolved the carbides at alloys with lower carbon content (1wt%), and resulted a homogeneous austenitic microstructure. The optimum results in the terms of tensile strength, elongation and impact toughness were obtained in solution annealed 1.0C-17Mn alloy, respectively, 865.57Mpa, 65.21% and 258 Joule. The wear test revealed that applied loads up to 10N should be considered as low stress wear while the higher as 15N should be considered as high stress wear. Therefore, 1C-21Mn alloy could be applied to relatively high stress wear conditions while the 1.3C-17Mn alloy could be only used under low stress wear conditions due to their insufficient impact toughness.